Legal Compliance with the Collection and Distribution of Sharia Banking Funds: A Study of Contracts, OJK Regulations and DSN-MUI Fatwa - Nanda Ega Rupita; Radi Erwandi; Nurnasrina (JAWI : Journal of Ahkam Wa Iqtishad, 2026)
Islamic banking as an integral part of the national financial system has a legal and sharia responsibility to ensure that all fundraising and distribution activities run according to the principles of fiqh muamalah. Legal compliance is a crucial aspect because every contract used, whether wadiah, mudharabah, murabahah, musyarakah, or ijarah—must not only meet the principles and requirements of the contract, but also be in line with the provisions of national regulations. This research is motivated by various phenomena of irregularities in the implementation of contracts that are still found in Islamic banking practices, such as routine wadiah grants, inaccuracies in the mudharabah ratio, murabahah practices without ownership of goods, and weaknesses in documentation and supervision in musyarakah and ijarah contracts. These inconsistencies show the need for an in-depth evaluation of the harmonization between Law No. 21 of 2008, the Financial Services Authority Regulation (POJK), and the DSN-MUI fatwa as the main legal source of the Islamic finance industry. This study aims to comprehensively analyze legal compliance in the collection and distribution of Islamic banking funds, by examining the suitability of wadiah and mudharabah contracts, the accuracy of the implementation of financing contracts, and the relationship between OJK regulations and DSN-MUI fatwas in forming legal certainty. The research methods used are normative legal research with a legislative approach, a fatwa approach, a conceptual approach, and a case study. The results of the study show that even though the legal framework and fatwa are fully available, the implementation of sharia compliance still faces challenges in the form of regulatory disharmony, limited sharia law literacy of bank human resources, and weak contract documentation. Harmonization between OJK regulations and DSN-MUI fatwas is an urgent need to create legal certainty, increase the effectiveness of sharia supervision, and strengthen the reputation and credibility of the Islamic banking industry in Indonesia.